2009
DOI: 10.1007/s11145-008-9158-2
|View full text |Cite
|
Sign up to set email alerts
|

The proper name as starting point for basic reading skills

Abstract: Does alphabetic-phonetic writing start with the proper name and how does the name affect reading and writing skills? Sixty 4- to 5½-year-old children from middle SES families with Dutch as their first language wrote their proper name and named letters. For each child we created unique sets of words with and without the child’s first letter of the name to test spelling skills and phonemic sensitivity. Name writing correlated with children’s knowledge of the first letter of the name and phonemic sensitivity for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
50
0
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 28 publications
12
50
0
6
Order By: Relevance
“…For example, children are generally able to write and spell their own names before other words (Levin, Both-de Vries, Aram, & Bus, 2005), and show a marked preference for including (often erroneously) letters from their own name when writing other words (Bloodgood, 1999;Both-de Vries & Bus, 2008;Treiman, Kessler, and Bourassa, 2001). The early focus on own-name letters, particularly the name's first letter, has been attributed to increased sensitivity to this sound-letter combination (e.g., Both-de Vries & Bus, 2010). It is also likely to reflect the extreme familiarity and positivity associated with one's own name (i.e., the 'name-letter effect ' -Nuttin, 1985).…”
Section: Self-referencing In Literacymentioning
confidence: 99%
“…For example, children are generally able to write and spell their own names before other words (Levin, Both-de Vries, Aram, & Bus, 2005), and show a marked preference for including (often erroneously) letters from their own name when writing other words (Bloodgood, 1999;Both-de Vries & Bus, 2008;Treiman, Kessler, and Bourassa, 2001). The early focus on own-name letters, particularly the name's first letter, has been attributed to increased sensitivity to this sound-letter combination (e.g., Both-de Vries & Bus, 2010). It is also likely to reflect the extreme familiarity and positivity associated with one's own name (i.e., the 'name-letter effect ' -Nuttin, 1985).…”
Section: Self-referencing In Literacymentioning
confidence: 99%
“…Results of the present study are supported by those of previous studies. A large body of research has shown that preschoolers with different cultural backgrounds and language structures have the ability to write their names though they do not know formal reading and writing (Both-de and Bus, 2010;Cabell et al, 2009;Chan and Louie, 1992;Levin et al 2005;Treiman et al, 2007;Villaume and Wilson, 1989;Yin and Treiman, 2013). In this study, it was seen that children were able to write the letters in their names and 35% of them were able to write all the letters of their names in the correct order.…”
Section: Discussionmentioning
confidence: 57%
“…Children during preschool realize their names and the letters in their names. They can distinguish their names among other words and are usually able to write their names (Both-de and Bus, 2010;Strickland and Shanahan, 2004;Treiman et al, 2007).…”
Section: Name Writing In Preschoolmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the work on young children's written communication has investigated the form or patterns in the marks or symbols or has looked at looked at specific skills such as writing letters of the alphabet or name writing (e.g. Clay, 1975;Both-de Vries, & Bus, 2010). Such research has drawn primarily from cognitive and socio-cognitive traditions.…”
Section: Introductionmentioning
confidence: 99%